Rapid Diagnostic Method for ZDJ9 Switch Machine Circuit Faults - YAN Yunfei; XU Jianjun; CAI Yijun (Chengshi guidao jiaotong yanjiu)
Objective The existing diagnostic methods for ZDJ9 switch machine circuit faults have multiple steps, complex operations, and low efficiency, seriously affecting the fault repair efficiency. Thus, it is necessary to develop a rapid diagnostic method for ZDJ9 switch machine circuit faults. Method Based on the composition of ZDJ9 switch machine circuit and the operation process of existing diagnostic methods, the issues with existing diagnostic methods are analyzed. A rapid diagnostic method for ZDJ9 switch machine circuit faults is proposed, the operation process and circuit principles of the method are described in detail. Compared with existing diagnostic methods, the advantages and disadvantages of this method are analyzed, as well as the application of this method on Shanghai Rail Transit Line 12. Result & Conclusion The above-mentioned rapid diagnostic method can quickly diagnose and identify indication circuit and action circuit faults. In diagnosing indication circuit, it does not require operating the turnout. While in diagnosing action circuits, it can narrow down the diagnostic range based on the correct indication circuit. Diagnosing the potential circuit hazards at the pre-operation position and confirming normal voltage before operation can prevent faults in advance. Practical application results show that this method significantly improves the efficiency of diagnosing circuit faults.